2015
DOI: 10.1371/journal.pone.0133231
|View full text |Cite
|
Sign up to set email alerts
|

Modest Interference with Actin Dynamics in Primary T Cell Activation by Antigen Presenting Cells Preferentially Affects Lamellal Signaling

Abstract: Dynamic subcellular distributions of signaling system components are critical regulators of cellular signal transduction through their control of molecular interactions. Understanding how signaling activity depends on such distributions and the cellular structures driving them is required for comprehensive insight into signal transduction. In the activation of primary murine T cells by antigen presenting cells (APC) signaling intermediates associate with various subcellular structures, prominently a transient,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…To investigate whether impaired cell couple maintenance results in loss of cytolytic effector function, Clone 4 CTLs were treated with a low concentration (40nM) of Jasplakinolide. At this concentration cell coupling was not impaired (25, 26), but the percentage of CTLs displaying a peripheral F-actin ring was markedly reduced to levels similar to those achieved among Clone 4 TILs (Fig. 3C to E, fig.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…To investigate whether impaired cell couple maintenance results in loss of cytolytic effector function, Clone 4 CTLs were treated with a low concentration (40nM) of Jasplakinolide. At this concentration cell coupling was not impaired (25, 26), but the percentage of CTLs displaying a peripheral F-actin ring was markedly reduced to levels similar to those achieved among Clone 4 TILs (Fig. 3C to E, fig.…”
Section: Resultssupporting
confidence: 63%
“…3F). Treatment with a higher concentration (100nM) of Jasplakinolide impaired cell coupling (25) and further reduced killing (Fig. 3F).…”
Section: Resultsmentioning
confidence: 98%
“…Costimulation is the principal amplifier of T cell signaling, which is evident from the reduced recruitment, in the absence of co-receptor signaling, of numerous signaling intermediates to two principal cellular structures that mediate T cell activation: a large, highly cross-linked protein complex at the center of the immunological synapse and a large actin-based lamellum that selectively forms during the first five minutes of cell coupling and traps smaller signaling complexes (6, 3133). To determine the importance of costimulation-controlled actin dynamics in driving such signaling organization, we asked whether the reduced localization of a prototypical element of T cell signaling upon costimulation blockade could be restored through the activation of WAVE2 and cofilin.…”
Section: Resultsmentioning
confidence: 99%
“…T cell activation stimulates the rapid and transient accumulation of T cell actin at the interface between the T cell and the APC (a region known as the immunological synapse) (1), which is coregulated by the TCR and CD28 (2). Genetic and pharmacological interference with T cell actin dynamics suggests that they are critical for many aspects of T cell function including APC coupling, spatiotemporal organization of T cell signaling, and regulation of transcription (26); however, the molecular mechanisms by which costimulation contributes to the regulation of T cell actin dynamics are unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the actin cytoskeleton in receptor clustering and in IS formation has been extensively studied (3,19,(46)(47)(48)(49)(50). In our own previous work, we found that the localization of TCRαβ molecules on microvilli is disturbed upon disruption of the actin cytoskeleton with latrunculin A (11).…”
Section: The Actin Cytoskeleton and Localization Of Membrane Proteinsmentioning
confidence: 95%